Building open source security into agile application builds. Issue 4 (April 2018) - Mackey, Tim
Abstract : Open source software offers many benefits, not least of which is the way that readily available software components and libraries can speed development. By not having to constantly reinvent the wheel, developers are able to adopt agile development methods that are adaptive, responsive – and fast. But there's also a risk involved. Using open source software offers many benefits and can speed development. But there are risks involved. Changes to applications are being made so quickly and so often that it is difficult to understand and review them for risk. And application development and security practices often appear to be at odds. To employ open source components safely, organisations need visibility into which components they're using. Tim Mackey of Black Duck by Synopsys examines how DevOps teams can utilise automated software composition analysis (SCA).